PE augmented mindfulness: A neurocognitive framework for research and future healthcare - David Sars; David Sars (Frontiers in Human Neuroscience, 2022)
Various well-controlled studies have suggested that practitioners in mindfulness can be prone to patient drop-out (e.g., due to chronic stress, pathology, cognitive reactivity), despite researchers having identified the underlying mechanisms that link mindfulness to mental health. In this article, a framework for physical exercise (PE) augmented mindfulness is proposed, which posits that consistently practiced PE before meditation can support (early-stage) mindfulness. Neurocognitive research shows PE (aerobic exercises or yoga) and mindfulness to impact similar pathways of stress regulation that involve cognitive control and stress regulation, thereby supporting the proposed synergistic potential of PE augmented mindfulness. Research focused on the psychophysiological impact of PE, showed its practice to promote short-term neurocognitive changes that can promote both cognitive control and the attainment of mindful awareness (MA). In order to chart dose responses required for protocol development, further research will be presented. Together these findings are discussed in light of future research on this multidisciplinary topic, protocol development, mindful walking, and further application in healthcare and beyond.